(untitled) (ART AND CULTURE BULLETIN, 2025)
The article discusses the connections between the stage and music, as well as the mastery of using musical and sound elements in the two-part documentary film «The Sound of the Kobyz - Witness of Centuries», filmed by «Karakalpakfilm» studio in 2023.